Analysis Of Output Voltage Profile Of Raindrop Impact Using Piezeolectric-Bridge Structure For Energy Harvesting - Hassan, Azlina (2016)

(untitled)
This research focuses on the output voltage profile generated from the piezoelectric-bridge structure for a single drop and continuous drop. In this study, a 5.6 mm of water droplet was used to impact the PVDF material (polyvinylidene fluoride) of 30 mm x 4 mm x 25 μm at different heights ranging from 0.3 m to 1.2 m. The output voltage profile for a single drop has shown a sinusoidal voltage whereas for continuous drop has shown no pattern as the voltage peaks were fluctuated. The experimental results show that a single drop generated higher peak-to-peak voltage compared with continuous drops, reaching a maximum of 10.08 V compared to 2.38 V. For both cases the peak-to-peak voltage increases as the height increase. In this study, the rate of decay of the output voltage profile was focused only on a single drop case due to the inconsistency of the output voltage profile for continuous drops. It can be seen that, the rate of decay decreases as the height decrease. The energy loss can be reduced at lower impact velocities as the raindrop impacted without splashes. It causes larger vibration on the piezoelectric material, which generates higher voltage. Finally, a comparison of analytical study between the experimental results and previous research findings has been done to compare the output voltage and the rate of decay of the output voltage. xi